Neuropeptide receptors provide a signalling pathway for trigeminal modulation of olfactory transduction. Issue 4 (3rd December 2012) - Daiber, Philipp; Genovese, Federica; Schriever, Valentin A.; Hummel, Thomas; Möhrlen, Frank; Frings, Stephan
Abstract: The mammalian olfactory epithelium contains olfactory receptor neurons and trigeminal sensory endings. The former mediate odor detection, the latter the detection of irritants. The two apparently parallel chemosensory systems are in reality interdependent in various well‐documented ways. Psychophysical studies have shown that virtually all odorants can act as irritants, and that most irritants have an odor. Thus, the sensory perception of odorants and irritants is based on simultaneous input from the two systems. Moreover, functional interactions between the olfactory system and the trigeminal system exist on both peripheral and central levels. Here we examine the impact of trigeminal stimulation on the odor response of olfactory receptor neurons. Using an odorant with low trigeminal potency (phenylethyl alcohol) and a non‐odorous irritant (CO2 ), we have explored this interaction in psychophysical experiments with human subjects and in electroolfactogram (EOG) recordings from rats. We have demonstrated that simultaneous activation of the trigeminal system attenuates the perception of odor intensity and distorts the EOG response. On the molecular level, we have identified a route for this cross‐modal interaction. The neuropeptide calcitonin‐gene related peptide (CGRP), which is released from trigeminal sensory fibres upon irritant stimulation, inhibits the odor response of olfactory receptor neurons. CGRP receptors expressed by these neurons mediate this neuromodulatory effect. This study demonstrates a site of trigeminal–olfactory interaction in the periphery. It reveals a pathway for trigeminal impact on olfactory signal processing that influences odor perception. Abstract : Co‐stimulation with an irritant attenuates odour perception. This can be shown with the floral odorant PEA and the irritant CO2 in human subjects. The effect is recapitulated in the rat olfactory system when the trigeminal peptide CGRP is co‐applied with PEA. This phenomenon is the result of a modulatory interaction between the olfactory and trigeminal systems in the nose. It is mediated by neuropeptide receptors expressed by olfactory receptor neurons.